Relationship between Seed Properties and Outcome Components for Selection Criteria of Corn (Zea Mays L.) Products at Various Dosages of Popostium Fertilizer - Vera Magdaleni Manullang; Aslim Rasyad; Dewi Indriyani Roslim (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
This research was conducted to determine the relationship between seed developmental characteristics and yield components in a population of maize (Zea mays L.) grown at different potassium fertilizer rates. The information could be utilized as alternative selection criteria for maize genotypes with high-yielding potential. This research was conducted at the Experimental field of the Horticulture Seed Agency, Pekanbaru. Seven maize genotypes with four potassium fertilizer rates were grown in a 350 cm x 200 cm experimental plot with three replications. The genotypes used were Bisi 228. Pertiwi 3. Bisi 2. Decoral, Bisi 18. Betras 4. and Srikandi. Potassium fertilizer rates included 30 kg, 50 kg, 70 kg, and 90 kg per ha, respectively. Traits observed were plant height, tesseling flowering date, silking date, seed dry accumulation rate, effective seed filling period, cob length, cob weight, number of seed rows, number of seeds per cob, seed weight per cob, the weight of 100 seeds and seed yield per m2. Analysis of variance was performed to the data using SAS and further tested by honesty significant difference at 5% level. Variance component, heritability, genetic correlation coefficient, and selection response were calculated for all characters and effective seed filling duration. The results indicated that the genetic variance component was significant for all characters except for the dry matter accumulation rate. All characters' heritability values were quite high except for effective seed-filling duration and the number of seeds per cob. Phenotypic correlation coefficients were positively significant between seed yield per m2 and plant height, seed development rate, cob length, ear weight, number of seeds per ear, seed weight per ear, and weight of 100 seeds. The genetic correlations was significant between seed yield per m2 and plant height, seed development rate, number of seeds per ear, and seed weight per ear. All characters' direct selection response value is higher than the indirect selection response value.